AB1348-HPR TELEMEDICINE IN RHEUMATOLOGY: ACCEPTANCE BY PATIENTS AND MEDICAL PRACTITIONERS IN GERMANY (TELERHEUMABB) - INTERIM ANALYSIS. (2nd June 2020) - Muehlensiepen, F.; Marquardt, W.; Knitza, J.; Hueber, A.; Welcker, M.
Abstract : Background: The number of rheumatologists in Germany does not cover the minimum medical need [1]. This implies long journeys and waiting periods for patients in the context of rheumatologists' consultations. International studies suggest that telemedicine could resolve these issues and support health care professionals in rheumatologic care [2, 3]. So far, comprehensive sustainable approaches are still pending in Germany. By addressing the potential users, TeleRheumaBB investigates whether and how telemedicine can support rheumatologic care in Germany. The study is realized from Oct. 2017 until Jun. 2020. Objectives: The objectives of the study are to evaluate the acceptance and willingness of patients and medical practitioners (MP) to implement telemedicine into rheumatological care as well as to understand how telemedical approaches should be designed to be applied in daily practice. Methods: The study design contains a mixed-methods approach, which combines qualitative and quantitative data. In the qualitative part of the study 28 in-depth interviews and 3 focus groups involving patients, rheumatologists, general practitioners and stakeholders were conducted. The quantitative part of the study comprised a questionnaire survey with rheumatologists (n=48) and referrers (n=444) and a second questionnaire survey with patients (n=734). Results: Qualitative Data : The term "telemedicine" is filled with different meanings. Motives to implement telemedicine into daily practice are patient guidance, information, substantial time savings, desire of a modern practice etc. Reported risks of telemedicine are adverse impacts on the doctor-patient-relationship as well as low benefit with high effort. Quantitative Data : 62% of the MPs' surveyed answered that they would like to use telemedical approaches. 81% of the participants supported doctor-doctor communication via telemedicine. Only 47% of the MPs' surveyed supported doctor-patients communication via telemedicine. MPs' state that there are barriers which prevent them from implementing telemedicine (89%). These are among others acquisition of technology, administrative expenses and poor remuneration. 53% of the patients surveyed stated that they had heard the term telemedicine before. 30% of the participants answered that they would like to try out telemedicine. 38% answered with "no" and 29% with "do not know". Further results from the patient survey will be available in June 2020. Conclusion: The study results show high acceptance rates of telemedicine regarding doctor-doctor communication. Doctor-patient communication via telemedicine is less accepted. However, MPs' are reporting obstacles preventing the implementation of telemedicine in rheumatology. In order to implement telemedicine in rheumatological care comprehensively, adequate conditions must be established in the German health care system. References: [1]Zink A, Braun J, Gromnica-Ihle E, Krause D, Lakomek HJ, Mau W, et al. Memorandum der Deutschen Gesellschaft für Rheumatologie zur Versorgungsqualität in der Rheumatologie – Update 2016. Zeitschrift für Rheumatologie. 2017;76(3):195-207. [2]McDougall J, Ferruci E, Glover J, Fraenkel L (2017) Telerheumatologiy: A Systematic Review. Arthritis Care Res (Hoboken); 69(10):1546-1557. [3]Piga M, Cangemi I, Mathieu A, Cauli A (2017) Telemedicine for patients with rheumatic diseases: Systematic review and proposal for research agenda. Semin Arthritis Rheum 47(1):121-128. Disclosure of Interests: Felix Muehlensiepen Grant/research support from: Novartis, Wenke Marquardt Grant/research support from: Novartis, Johannes Knitza Grant/research support from: Research Grant: Novartis, Axel Hueber Grant/research support from: Novartis, Lilly, Pfizer, EIT Health, EU-IMI, DFG, Universität Erlangen (EFI), Consultant of: Abbvie, BMS, Celgene, Gilead, GSK, Lilly, Novartis, Speakers bureau: GSK, Lilly, Novartis, Martin Welcker Grant/research support from: Abbvie, Novartis, UCB, Hexal, BMS, Lilly, Roche, Celgene, Sanofi, Consultant of: Abbvie, Actelion, Aescu, Amgen, Celgene, Hexal, Janssen, Medac, Novartis, Pfizer, Sanofi, UCB, Speakers bureau: Abbvie, Aescu, Amgen, Biogen, Berlin Chemie, Celgene, GSK, Hexal, Mylan, Novartis, Pfizer, UCB